Improvement of Aspergillus niger for Sodium Gluconate Synthesis by UV Mutation Method - Rajagopalan Prabu; Thomas Chand; Sunhare Raksha (E-Journal of Chemistry)
The sodium gluconate synthesis pathway was improved in Aspergillus niger by random mutation method. A. niger was mutated with Ultraviolet (UV) radiation and the alteration of cell bound enzymes activity of gluconic acid synthesis pathway and sodium gluconate synthesis were evaluated. The improved mutants (A. niger UV-112) was capable of producing sodium gluconate up to final concentrations of 60 g/L in batch fermentation, which was 3.0 fold higher than the parent strain. It have been observed that the changes in activities of cell bound enzymes related for gluconic acid pathway such as glucose dehydrogenase and glucose oxidase and it were significantly higher than the parent strain. The mutant A. niger strain and the simple method used to decrease the production cost and development of fermentation process for industrial production of gluconic acid or its salt.